Built to last: population aging and long run development in metropolitan Europe. (16th February 2015) - Gagliardi, Luisa; Percoco, Marco
The paper examines the role of demography on the growth perspectives of European metropolitan areas. Our findings are in support of the key role played by the demographic structure of the population in determining the economic prospects of European cities. Regions and cities with higher levels of dependency ratios are found to show lower growth rates, in the long run. This evidence supports earlier findings on the relevance of population age on both aggregate productivity changes and the human capital stock of the local labour force.